(untitled) (Research, Society and Development, 2023)
Galactosemia is known as an inborn error of metabolism, which is unable to digest galactose, sugar present in breast milk, which is the main source of nutrients for infants. The treatment carried out in the first months of life consists of suspending the intake of breast milk, using infant formulas. The present study is configured as an integrative literature review. It used scientific materials published online by entities linked to scientific research. Among the review methods, the present study opted for the integrative modality and the research strategy was defined with the help of PICO (patient, intervention, comparison and outcomes). P: infants with galactosemia; I: use of formulas as a substitute for breast milk; C: infants with galactosemia who started using soy-based formulas; O: effect of formulas on symptoms and complications of galactosemia. Data collection was carried out between February and May 2023 and was guided by the following question: “What is the best option for infant formula for infants with galactosemia, as well as its effects on improving symptoms?”. The objective of the article was to analyze the indications for the use of infant formulas as a substitute for breastfeeding in babies diagnosed with galactosemia, as well as their types and benefits to treatment. The work failed to demonstrate better effectiveness among the formula options available and highlighted the need for further studies on the object of study.